THE ROLE OF INDY IN METABOLIC REGULATION - Diana M Willmes; Andreas L Birkenfeld (Computational and Structural Biotechnology Journal, 2013)
Reduced expression of the Indy (I'm Not Dead Yet) gene in D. melanogaster and C. elegans extends longevity. Indy and its mammalian homolog mINDY (Slc13a5, NaCT) are transporters of TCA cycle intermediates, mainly handling the uptake of citrate via the plasma membrane into the cytosol. Deletion of mINDY in mice leads to significant metabolic changes akin to caloric restriction, likely caused by reducing the effects of mINDY-imported citrate on fatty acid and cholesterol synthesis, glucose metabolism and ß-oxidation. This review will provide an overview on different mammalian SLC13 family members with a focus on mINDY (SLC13A5) in glucose and energy metabolism and will highlight the role of mINDY as a putative therapeutic target for the treatment of obesity, non-alcoholic fatty liver disease and type 2 diabetes.